Recovery of residual crude palm oil from the empty fruit bunch spikelets using environmentally friendly process - Gomez, Javier Chavarro; Mokhtar, Mohd Noriznan; Sulaiman, Alawi; Baharuddin, Azhari Samsu; Busu, Zainuri (Taylor and Francis, 2015)
The development of new, low-cost technology to increase the oil recovery in the palm oil mill especially from the palm oil wastes has been an important goal for the industry to increase OER. According to preliminary oil detection, the residual oil is mainly located on the surface of spikelet, about 73.73 ± 0.05% from total residual oil. The combined water-steam shows the best oil extraction process, indicating 82 ± 0.13% of oil may be removed from the EFB spikelet. Thus, this method is chemical free and environmentally friendly residual CPO recovery process using EFB.